The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2012
DOI: 10.1590/s0103-84782012000300019
|View full text |Cite
|
Sign up to set email alerts
|

Ensaio biomecânico da túnica albugínea bovina conservada em glicerina 98% para utilização como membrana biológica

Abstract: 501Ensaio biomecânico da túnica albugínea bovina conservada em glicerina 98% para utilização como membrana biológica.Ciência Rural, v.42, n.3, mar, 2012. Ciência Rural, Santa Maria, v.42, n.3, p.501-506, mar, 2012 ISSN 0103-8478

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 4 publications
(3 reference statements)
0
6
0
Order By: Relevance
“…Obtaining a satisfactory result compared to placebo treatment, in relation to hoof growth rate, spatial relationship between the third phalanx and the corneal case, vascular perfusion and lamellar healing process. Biological membranes derived from animal tissues have been studied and used mainly in surgical repairs of hernias in veterinary medicine (Vidor et al 2013;Marques et al 2015) and as dressings for external wounds and grafts (Aceto et al 2007;Queiroz et al 2012). In the present work, biological membranes derived from bovine tunica albuginea were used in conjunction with tenorrhaphy, with the aim of evaluating their ability to aid healing.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Obtaining a satisfactory result compared to placebo treatment, in relation to hoof growth rate, spatial relationship between the third phalanx and the corneal case, vascular perfusion and lamellar healing process. Biological membranes derived from animal tissues have been studied and used mainly in surgical repairs of hernias in veterinary medicine (Vidor et al 2013;Marques et al 2015) and as dressings for external wounds and grafts (Aceto et al 2007;Queiroz et al 2012). In the present work, biological membranes derived from bovine tunica albuginea were used in conjunction with tenorrhaphy, with the aim of evaluating their ability to aid healing.…”
Section: Discussionmentioning
confidence: 99%
“…The testicles, in general, have a thin capsule of connective tissue called the tunica albuginea, which does not present much difference in its histological architecture and anatomy among domestic animal species. It is composed of dense connective tissue, characterized by a greater quantity of collagen fibers and a smaller number of cells, compared to loose connective tissue (QUEIROZ et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Biomaterials such as acellular bladder matrix (ZHAO et al, 2015;LI et al, 2016), pericardium (ALBRECHT et al, 2015), tunica vaginalis (WONGSETTHACHAI et al, 2011;FARIA et al, 2020), swine intestinal submucosa (ROSSETTO et al, 2013), peritoneum (OLIVEIRA et al, 2008), amniotic membrane (IIJIMA et al, 2007;ADAMOWICZ et al, 2012) and ileum (FERREIRA et al, 2005) have been reported in bladder repair surgery. Several studies have shown the tunica albuginea as a useful biomaterial due to its low cost, easy collection, conservation, and processing (QUEIROZ et al, 2012;OLIVEIRA et al, 2015;MORAES et al, 2017.…”
Section: Introductionmentioning
confidence: 99%
“…Tunica albuginea is a thick capsule of dense connective tissue, which surrounds the testicle (JUNQUEIRA & CARNEIRO, 2017). It is rich in collagen fibers organized in two layers: the external has longitudinal collagen fibers orientation and the internal layer has circularly bundle dispositions, which enable tissue tensile strength (QUEIROZ et al, 2012). Considering that bovine tunica albuginea is an available, easy handling and inexpensive biomaterial, this research was motivated by the lack of reports of its use as xenograft in rats' urinary vesicle.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, a scaffold with a mechanical force that facilitates the regeneration process and amplifies bladder capacity and complacency is required [8]. In this regard, some studies had good results using tunica albuginea biomaterial as tissue engineering [9][10][11][12][13]. The tunica albuginea is a thick capsule of connective tissue, composed of two layers of collagen bundles [14,15].…”
Section: Introductionmentioning
confidence: 99%